Utilization of plastic waste to improve properties of road material: A review - Safety Husna Pangestika; Kushendarsyah Saptaji; Anak Agung Ngurah Perwira Redi; Asep Bayu Dani Nandiyanto; Surya Danusaputro Liman; Farid Triawan (Universitas Muhammadiyah Magelang, 2023)
The failure of asphalt pavement occurs due to heavy traffic loads and weather conditions such as humidity, temperature, and UV radiation. To address or minimize these failures, significant efforts have been made in recent years to improve the properties of asphalt materials, ultimately enhancing field performance, and extending the lifespan of pavements. Asphalt with plastic modification is considered one of the most suitable and popular approaches. Plastic offers several advantages and is generally known to improve stiffness at high temperatures, although some types are more susceptible to phase separation. Therefore, it is necessary to use the right methods, temperatures, and proportions when designing plastic asphalt mixes to produce a homogeneous mixture. Plastic mixing with asphalt blends is done through two methods: the dry mixing method and the wet mixing method. The ideal amount of plastic added to the mix should modify the asphalt blend to make it more resistant to rutting, fatigue cracking, thermal cracking, and moisture resistance. Failure to determine the correct plastic dosage can lead to negative effects on pavement performance. In general, incorporating plastic waste into asphalt mixes has shown improvements in performance metrics such as stiffness, resistance to cracking, and fatigue resistance. The result of the asphalt and plastic mixture is an increase in stability, making the mixture stronger in bearing loads. Adding plastic waste to the mix makes it stiffer, resulting in a higher MR value, thus providing better resistance to permanent deformation compared to conventional mixtures. Additionally, in wheel tracking tests, the asphalt-plastic mixture reduced rutting depth by 29% compared to conventional mixtures. Similarly, in fatigue testing, the asphalt-plastic mixture yielded a higher load cycle value, making it more resistant to repeated loads. This article explains the details of using plastic in asphalt mixes to enhance asphalt performance and road durability. Various types of plastics, including PET, HDPE, LDPE, PVC, LDPE, PP, and PS, have been successfully used to modify asphalt. However, each type has its advantages and disadvantages, as discussed comprehensively in this journal. Essentially, the utilization of plastic waste in asphalt blends will help reduce the need for landfill disposal, decrease dependence on non-renewable resources, and expand options for asphalt pavement construction.